2020
DOI: 10.1111/vco.12602
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of canine CD20 chimeric antigen receptor T cell manufacturing and in vitro cytotoxic activity against B‐cell lymphoma

Abstract: Canine B-cell lymphoma is one of the most common haematopoietic neoplasms in veterinary medicine, and it is considered a relevant model for human diffuse large Bcell lymphoma. Although the standard treatment consisting of multi-drug chemotherapy is effective in most cases, treatment is often challenging because of relapse and drug resistance. The adoptive transfer of autologous T cells genetically modified to express a CD19-specific chimeric antigen receptor (CD19 CART cells) has been shown to be highly effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The method below provides step-by-step details to effectively engineer primary canine T cells. Compared to previously published methods ( Panjwani et al., 2020 ; Sakai et al., 2020 ), our implemented protocol based on use of RD114 pseudotyped viral vectors and activation of canine T lymphocytes via anti-canine CD3/CD28-coated beads enables high transduction efficiencies using a single infection. Of note, we have also successfully employed chimeric RD114 and VSVG pseudotyped retrovirus for canine T cell transduction.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…The method below provides step-by-step details to effectively engineer primary canine T cells. Compared to previously published methods ( Panjwani et al., 2020 ; Sakai et al., 2020 ), our implemented protocol based on use of RD114 pseudotyped viral vectors and activation of canine T lymphocytes via anti-canine CD3/CD28-coated beads enables high transduction efficiencies using a single infection. Of note, we have also successfully employed chimeric RD114 and VSVG pseudotyped retrovirus for canine T cell transduction.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Although several types of CAR-T cell therapies have already been approved in humans [104], there are still no approved CAR-T cell therapies for dogs. However, several groups, including our own, have already reported on how to create canine CAR-T cells with some efficacy in vitro [105] and in vivo [106][107][108]. To maximize the effect of CAR-T cell therapy in patients, CAR-T cells must be administered after myelosuppression using strong anticancer drugs and radiation to eliminate the immune cells.…”
Section: Next Generations Of Immunotherapy In Dogsmentioning
confidence: 99%
“…In 2020, a group based out of Yamaguchi, Japan demonstrated that an anti‐CD20 CAR could be stably transduced into canine T cells via a retrovirus vector 48 . Their paper provides data on a variety of optimization experiments they used, comparing how canine CAR‐T cells were differentially transduced, activated, and expanded with a variety of methods, including various agonist antibodies (anti‐CD3, anti‐CD28), cytokines, phytohemagglutinin, aAPCS, and different transduction modes.…”
Section: Chimeric Antigen Receptor‐t Cellsmentioning
confidence: 99%